Genetic diversity and development of high fiber yield kenaf (Hibiscus cannabinus L.) mutant hybrids through diallel crosses - Al-Mamun, Md. (2022)
Kenaf (Hibiscus cannabinus L.) is an economically important fiber crop globally for multipurpose industrial uses such as paper making, car interior components and building boards. However, commercial cultivation of this fiber crop in Malaysia has limitations due to lack of superior varieties with high fiber yield. This study was conducted to assess the genetic diversity among kenaf mutants based on agro-morphological traits and molecular markers diversity, analyze the combining ability of the selected parents and hybrids, and estimate heterosis and the nature of gene actions. To achieve these objectives, field trials and molecular diversity works were conducted at Universiti Putra Malaysia (UPM), Serdang, Selangor, Malaysia, between 2019 and 2021. Data were collected on the eight qualitative and 15 quantitative traits of the 31 kenaf genotypes. The analysis of variance over two evaluation seasons showed significant differences among genotypes for all traits except for stem top diameter. According to principal component analysis (PCA), the first five PCA accounted for 85.16% variation between genotypes based on a correlation matrix of all the quantitative traits. The mutant lines derived from V36 parental variety were grouped into six clusters, indicating a wide range of genetic variability. Path coefficient analysis revealed the maximum contribution of fresh stem weight without leaves and pod to fiber yield, followed by plant height. For molecular characterization, 10 out of the 72 expressed sequence tags - simple sequence repeat (EST-SSR) primers produced clear polymorphic bands with a mean value of 5.2 alleles per primer. These EST-SSR primers were found to be extremely informative, suggesting that among the 31 genotypes were genetically diverse. The polymorphism information content (PIC) value ranged from 0.531 to 0.737, with a mean of 0.610, indicating that the genotypes are genetically diverse. Shannon index estimation varied from 0.982 to 1.515 among 31 genotypes, whereas 0.123 to 0.405 was recorded within the early, intermediate and mid-late flowering groups. Genetic differentiation ranged from 0.67 to 1.0 alongside the average gene flow (Nm) of 0.024. The analysis of molecular variance (AMOVA) revealed 76% variation within three flowering groups., while among the groups recorded was 24%. Based on the unweighted pair group method with arithmetic means (UPGMA) dendrogram the evaluated kenaf mutants were clustered into five major groups based on EST-microsatellites data. Combining phenotypic and molecular data in the selection of parents for hybridization activities would yield a more accurate summary and the cluster analysis identified eight mutant lines (G5, G9, G13, G21, G22, G24, G30 and G31) and one inbred (G28) that were selected for hybrid crossing using a half diallel method. The genotypes were chosen as parental sources from each heterotic group at the genetic and phenotypic levels on genetic distances and several important agronomic traits. Thirty-six hybrids were successfully produced from nine morphologically distinct kenaf genotypes using half diallel mating design. Field trials were carried out in two environments to evaluate the yield performance of 36 F1 hybrid crosses and nine parental lines using seven qualitative and 15 quantitative attributes. From the combined data of the two environments, the combining ability analysis revealed significant general combining ability (GCA) for all traits except stem top diameter, and significant specific combining ability (SCA) for all traits except plant height and stem top diameter. The result indicated that additive and non-additive gene actions were involved in the genetic control of the traits. The magnitude of GCA variance was considerably higher than that of SCA variance except for stem top diameter, node number, and fresh stem weight with leaves and pod, showing that additive gene action predominates for these traits. The parental lines P1 (G5: ML5), P3 (G13: ML36-10) and P4 (G21: ML36-24) had outstanding general combiners for fiber yield and yield-related traits. Most traits showed over-dominant gene action, except for plant height, stem middle diameter, stem top diameter, days to first flowering, dry stick weight, dry fiber weight and 1000 seed weight, which showed a partial dominance. Considering specific combining ability and heterosis values, the crosses P1 (G5) × P4 (G21), P1 (G5) × P9 (G31), P2 (G9) × P3 (G13), P2 (G9) × P5 (G22), P4 (G21) × P6 (G24), P4 (G21) × P7 (G28), P4 (G21) × P9 (G31), P5 (G22) × P8 (G30), and P7 (G28) × P9 (G31) were high heterotic response for fiber yield, stick yield, number of pods per plant and smaller seed size. The nine hybrids are recommended for further evaluation at multilocation trials to select several superior hybrids with high fiber yield for commercial cultivation in Malaysia.